Label-free quantitative proteomics unravels the importance of RNA processing in glioma malignancy. (20th May 2017) - Bi, Baibin; Li, Feng; Guo, Jisheng; Li, Cuiling; Jing, Ruirui; Lv, Xin; Chen, Xinjun; Wang, Fengqin; Azadzoi, Kazem M.; Wang, Lin; Liu, Yuguang; Yang, Jing-Hua
Highlights: Quantitative proteomics on different grades of glioma was performed. A list of differentially expressed proteins was identified. Importance of RNA processing in glioma malignancy was revealed. RNA processing links with crucial signal transduction and neuronal function and activity. Representative proteins were validated by immune assay. Abstract: Glioma, one of the most common cancers in human, is classified to different grades according to the degrees of malignancy. Glioblastoma (GBM) is known to be the most malignant (Grade IV) whereas low-grade astrocytoma (LGA, Grade II) is relatively benign. The mechanism underlying the pathogenesis and progression of glioma malignancy remains unclear. Here we report a quantitative proteomic study to elucidate the differences between GBM and LGA using liquid chromatography and tandem mass spectrometry followed by label-free quantification. A total of 136 proteins were differentially expressed in GBM for at least five folds in comparison with LGA. Ontological analysis revealed a close correlation between GBM-associated proteins and RNA processing. Interaction network analysis indicated that the GBM-associated proteins in the RNA processing were linked to crucial signaling transduction modulators including epidermal growth factor receptor (EGFR), signal transducer and activator of transcription 1 (STAT1), and mitogen-activated protein kinase 1 (MAPK1), which were further connected to the proteins important for neuronal structural integrity, development and functions. Upregulation of 40S ribosomal protein S5 (RPS5), Ferritin Heavy chain (FTH1) and STAT1, and downregulation of tenascin R (TNR) were validated as representatives by immune assays. In summary, we revealed a panel of GBM-associated proteins and the important modulators centered at the RNA-processing network in glioma malignancy that may become novel biomarkers and help elucidate the underlying mechanism.